Rheological, Mechanical, Microstructural and Radiation Shielding Properties of Cement Pastes Containing Magnetite (Fe3O4) Nanoparticles - Pawel Sikora; Ahmed M. El-Khayatt; H. A. Saudi; Maxime Liard; Didier Lootens; Sang-Yeop Chung; Paweł Woliński; Mohamed Abd Elrahman (International Journal of Concrete Structures and Materials, 2023)
Abstract This work examines the influence of iron oxide nanoparticles (Fe3O4 NPs) on neutron and gamma-ray radiation shielding characteristics of Portland cement paste. Experimental evaluations were supplemented with theoretical studies using NXCom program. Portland cement pastes with 5, 10, 15, 20, and 30 wt% of nanomagnetite cement replacement were produced. Moreover, rheological, early strength development, compressive strength, and mercury intrusion porosimetry (MIP) tests were performed. The results showed that increasing the amount of Fe3O4 NPs in a mix leads to a gradual increment in measured viscosity and yield stress. High nano-Fe3O4 content substantially impeded the early strength development process and led to a decrement in the 7- and 28-day compressive strength of cement paste. The MIP studies exhibited a gradual increment in total porosity, and average pore volume, as nano-Fe3O4 content was increased. All the macroscopic cross-sections of slow, fast and thermal neutrons constantly increased as a result of the addition of magnetite nanoparticles, with their variations being markedly linear. Similarly, gamma attenuation test results indicated that the addition of Fe3O4 powder enhances the shielding capability of paste in the energy range of interest (0.08–2.614 MeV). In conclusion, Fe3O4 nanoparticles can be successfully used in producing lead-free cementitious composites with improved gamma-ray and neutron shielding properties. However, certain drawbacks related to an increment in matrix porosity and thus a decrement in mechanical performance should be taken into account.